Uji Stabilitas Sediaan Krim Ekstrak Daun Belimbing Wuluh (Averhoa blimbi L.) dengan Variasi Konsentrasi Emulgator - Maulita Saraswati; Gigih Kenanga Sari; Wahyu Purwanjani (Joseph: Journal of Science and Pharmacy, 2023)
Background: Belimbing wuluh (Averrhoa bilimbi L.) has been widely utilized as a traditional medicinal ingredient due to its antioxidant and anti-inflammatory properties. A stable cream preparation formulation is very important to maintain the effectiveness of its active ingredients. Therefore, this study aims to evaluate the physical stability of Belimbing wuluh leaf extract cream preparation with variations in emulgator concentration. Purpose: To determine the effect of varying TEA concentration on cream stability, determining the effect of variations in stearic acid concentration on cream stability, determining the optimal concentration of TEA and stearic acid to obtain a stable cream formulation. Method: This study used an experimental method with a cream formulation containing stearic acid (10%, 12%, 14%) and triethanolamine (TEA) (4%, 5%, 6%). Stability evaluation was done through organoleptic test, pH, viscosity, spreadability, adhesiveness, and cycling test. Results: The cream preparation showed good homogeneity with a light brown color and characteristic odor of the extract. The pH value ranged from 7.50 to 8.04, in accordance with topical cream standards. Viscosity increased as the concentration of stearic acid and TEA increased. Spreadability and stickiness decreased after the accelerated stability test, but remained within acceptable limits. Conclusion: Cream formulations with a combination of stearic acid and TEA provide good physical stability. The formula with 14% stearic acid and 6% TEA showed more optimal physical characteristics than the other formulas